A kind of antistatic PC / ABS alloy material containing compatibilizer and preparation method thereof
By using homemade antistatic agents and inorganic staple fiber compositions in PC/ABS alloy materials, combined with the dispersion and mixing technology of the intensive refining stage, the problems of general mechanical properties and poor antistatic properties of existing materials are solved, and the multi-performance improvement of the material and the reduction of production costs are achieved.
Patent Information
- Application Number
- CN202410746213.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-11
AI Technical Summary
The existing PC/ABS alloy materials have problems such as general mechanical properties and relatively poor antistatic properties, and the cost is high when adding graphene as an antistatic agent and weak long-lasting performance.
The homemade antistatic agent is used to combine the inorganic staple fiber composition and toughening agent, and the compatibility agent, toughening agent, inorganic staple fiber composition, antistatic agent, coupling agent, anti-aging agent and PC resin and ABS resin are dispersed and mixed with PC resin and ABS resin through the refining stage to prepare PC/ABS alloy materials with good antistatic properties, thermal conductivity, mechanical strength, impact toughness and anti-aging properties.
The antistatic and thermal conductivity of PC/ABS alloy materials has been improved, and it has good mechanical strength, impact toughness and anti-aging properties, and the production cost is relatively low.
Smart Images

Figure BDA0004886528060000191 
Figure BDA0004886528060000201 
Figure BDA0004886528060000211
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS alloy material preparation, in particular to an antistatic PC / ABS alloy material containing a compatibilizer and a preparation method thereof. Background Art
[0002] Polycarbonate PC has good mechanical properties, heat resistance and excellent impact toughness. It is a non-crystalline engineering plastic with a transparent appearance and excellent comprehensive performance. It is widely used in machinery, automobiles, electronic appliances, packaging materials and other technical fields. Although polycarbonate PC has excellent performance in some aspects, it contains polar ester groups and the molecular chain is relatively rigid, resulting in its rigidity but poor flexibility. The high melting point leads to poor extrusion processing performance. In addition, polycarbonate PC has poor fluidity, which makes it difficult to manufacture large thin-walled products, and the residual stress after molding is large, and the product is prone to stress cracking.
[0003] ABS resin is made by grafting polybutadiene rubber (PB), styrene (S) and acrylonitrile (A), in which polybutadiene rubber PB gives ABS resin good overall thermal stability, acrylonitrile S gives ABS resin good overall toughness and impact resistance, and styrene S gives ABS resin good overall rigidity and processability. Although ABS resin has excellent overall performance, high impact strength at low temperatures, and good dimensional stability, it is also one of the widely used engineering plastics. However, compared with polycarbonate PC, it can be seen that ABS resin has the advantages of good molding and low cost, but its disadvantages are relatively poor impact toughness and heat resistance. In order to improve the impact toughness and heat resistance of ABS resin, polycarbonate PC is usually used to modify ABS resin. PC / ABS alloy material. PC / ABS alloy material has the excellent properties of both polycarbonate PC and ABS resin, making it widely used in automotive interior parts, communication equipment, household appliances, lighting equipment and other scenes.
[0004] At present, the PC / ABS alloy material in the prior art includes PC resin, ABS resin, toughening agent MBS, short glass fiber, dispersant, and antioxidant. The mass ratio of PC resin to ABS resin is (12-16): (60-70); the content of toughening agent MBS is 3-8wt%; the content of short glass fiber is 15-20wt%, the content of dispersant is 0.1-2.0wt%, and the content of antioxidant is 0.5-1.0wt%. The tensile strength of PC / ABS alloy material is 40-65MPa, the bending strength is 40-70MPa, and the notched impact strength is 20-40KJ / m 2 , elongation at break is 3-8%, surface resistivity is 10 9 Ω or more.
[0005] With respect to the PC / ABS alloy materials in the above-mentioned related art, the applicant has found that the PC / ABS alloy materials have the problem of general mechanical properties and relatively poor antistatic properties. Although adding 2-4wt% graphene as an antistatic agent to the existing PC / ABS alloy materials can improve the overall surface resistivity, the cost of graphene is relatively high and it is easy to migrate to the surface and wear and tear. The overall production cost of the prepared PC / ABS alloy material with antistatic effect is relatively high and the antistatic durability is relatively weak. In order to solve the above problems, the present invention provides an antistatic PC / ABS alloy material containing a compatibilizer and a preparation method thereof. Summary of the invention
[0006] In order to solve the technical defects of the existing PC / ABS alloy materials with antistatic effect, such as high overall production cost and weak antistatic durability, the present invention provides an antistatic PC / ABS alloy material containing a compatibilizer and a preparation method thereof.
[0007] The present invention provides an antistatic PC / ABS alloy material containing a compatibilizer, which is achieved by the following scheme:
[0008] An antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by weight: 80-100 parts of PC resin, 20-25 parts of ABS resin, 5-10 parts of toughening agent, 4-8 parts of compatibilizer, 20-30 parts of inorganic staple fiber composition, 4-8 parts of antistatic agent, 0.5-2 parts of coupling agent, and 1-4 parts of anti-aging agent;
[0009] The compatibilizer is ABS-g-MAH and / or styrene-grafted maleic anhydride multipolymer;
[0010] The antioxidant includes antioxidant and anti-ultraviolet agent;
[0011] The antioxidant is composed of antioxidant 1098, antioxidant 168, silicon carbide whiskers and / or nano silicon nitride;
[0012] The anti-ultraviolet agent is composed of UV-531, UV-234 and titanium nitride;
[0013] The coupling agent is composed of a siloxane coupling agent and a titanate coupling agent;
[0014] The toughening agent is at least one of TPU, TPEE, TPV and MBS;
[0015] The inorganic short fiber composition comprises short glass fibers and short silicon carbide fibers.
[0016] The PC / ABS alloy material prepared by using a homemade antistatic agent, an inorganic short fiber composition and a toughening agent in the present invention not only has good antistatic properties and thermal conductivity, but also has good mechanical strength, impact toughness and aging resistance.
[0017] Preferably, the antistatic PC / ABS alloy material is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent, 6 parts of compatibilizer, 28 parts of inorganic staple fiber composition, 6 parts of antistatic agent, 2 parts of coupling agent, and 3 parts of antioxidant.
[0018] By adopting the above technical solution, the prepared PC / ABS alloy material has good antistatic properties, thermal conductivity, mechanical strength, impact toughness and aging resistance, while also having the advantages of excellent processing performance and relatively economical production cost.
[0019] Preferably, the inorganic staple fiber composition is composed of chopped glass fibers, chopped silicon carbide fibers, and amino-treated carbon nanotubes in a mass ratio of (30-40):(50-65):(5-10); the chopped glass fibers include chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm; the chopped silicon carbide fibers include chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm.
[0020] By optimizing the ratio of chopped glass fiber, chopped silicon carbide fiber and amino carbon nanotubes and controlling the length distribution of chopped glass fiber and chopped silicon carbide fiber, the mechanical strength, impact toughness and thermal conductivity of PC / ABS alloy materials can be improved.
[0021] Preferably, the chopped glass fibers are composed of chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
[0022] Preferably, the chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
[0023] By optimizing the length distribution of chopped glass fiber and chopped silicon carbide fiber and the mass composition of chopped glass fiber and chopped silicon carbide fiber of various lengths, the mechanical strength, impact toughness and thermal conductivity of PC / ABS alloy materials can be further improved.
[0024] Preferably, a conductive film is formed on the surface of the chopped glass fibers; the conductive film is at least one of a polyaniline conductive film, a deposited metal film, and a conductive oxide film; the deposited metal film is one of silver, copper, and aluminum.
[0025] By adopting the above technical solution, the thermal conductivity of PC / ABS alloy materials can be further improved.
[0026] Preferably, the antistatic agent is graphene-doped modified polyaniline resin and / or carbon nanotube-doped modified polyaniline resin.
[0027] Preferably, the preparation method of the antistatic agent comprises the following steps:
[0028] Step 1, obtaining surface activated graphene and / or surface activated carbon nanotubes: performing surface activation treatment on graphene and / or carbon nanotubes so that one of hydroxyl groups, carboxyl groups and amino groups are generated on the surface of graphene and / or carbon nanotubes; or purchasing commercially available surface activated graphene and / or surface activated carbon nanotubes;
[0029] Step 2: 1 part by mass of carboxylated graphene and / or carboxylated carbon nanotubes is added to 20-25 parts by mass of deionized water, and then mechanically stirred for 5-10 minutes and ultrasonically dispersed for 3-6 hours to obtain an aqueous dispersion of graphene and / or carbon nanotubes;
[0030] Step 3: Dissolve 6-12 parts by weight of aniline in 100-200 parts by weight of 1-2 mol / L hydrochloric acid aqueous solution to prepare an aniline solution; slowly drop the graphene and / or carbon nanotube aqueous dispersion into the aniline solution under magnetic stirring and nitrogen protection; continue magnetic stirring for 8-24 hours after the dropwise addition to obtain a gray-black mixed emulsion;
[0031] Step 4, cooling to 0-4°C in an ice bath, maintaining the temperature of the gray-black mixed emulsion between 0-4°C, adding 200-400ppm of initiator to the gray-black mixed emulsion under magnetic stirring, continuing magnetic stirring for 12-16h, maintaining the temperature of the gray-black mixed emulsion between 0-4°C and standing for 18-24h, polymerizing to obtain a solution containing a black-green precipitate, then vacuum filtering to obtain a black-green precipitate, washing the black-green precipitate three times with deionized water and ethanol alternately, and after vacuum drying the obtained black-green precipitate, placing it in a planetary ball mill for ball milling for 15-30min to obtain the product antistatic agent.
[0032] By adopting the above technical solution, the thermal conductivity and heat conduction performance of the prepared PC / ABS alloy material can be effectively improved. In addition, the production cost of the antistatic agent prepared in the present invention is relatively low compared to graphene, which is convenient for popularizing and promoting antistatic PC / ABS alloy materials.
[0033] Preferably, the coupling agent is composed of a composite siloxane coupling agent and di(dioctylpyrophosphoryl)ethylene titanate in a mass ratio of (8-9):(1-2); the composite siloxane coupling agent is prepared by reflux reaction of methacryloxysilane and aminosilane at 70-90°C for 2-4h.
[0034] By adopting the above technical scheme, the dispersion uniformity of the inorganic staple fiber composition and the antioxidant can be effectively improved, thereby ensuring that the prepared PC / ABS alloy material has good electrical and thermal conductivity, mechanical strength, impact toughness and anti-aging properties.
[0035] The present invention provides a method for preparing an antistatic PC / ABS alloy material containing a compatibilizer, which is achieved by the following technical scheme: A method for preparing an antistatic PC / ABS alloy material containing a compatibilizer, comprising the following steps:
[0036] Step 1, preparing a surface-modified inorganic staple fiber composition and an antistatic agent at the same time;
[0037] Step 2: uniformly mix the accurately measured PC resin, ABS resin, compatibilizer, toughening agent, surface-modified inorganic staple fiber composition, antistatic agent, coupling agent, and antioxidant, and then knead at 215-220° C. for 240-360 seconds to obtain a fluidized kneaded mixture;
[0038] Step three, putting the fluidized banburying mixture into a twin-screw extruder for melt extrusion, the temperature setting of the seven heating zones of the twin-screw extruder is as follows: zone one 200-210°C, zone two 220-230°C, zone three 235-240°C, zone four 245-250°C, zone five 250-255°C, zone six 250-255°C, zone seven 250-255°C, the screw speed is 300-500rpm, and the obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain an antistatic PC / ABS alloy material.
[0039] In the preparation method of the present invention, the compatibilizer, toughening agent, inorganic short fiber composition with surface modification, antistatic agent, coupling agent, anti-aging agent, PC resin, ABS resin and compatibilizer are dispersed and mixed uniformly through the mixing stage, thereby ensuring that the prepared PC / ABS alloy material has good electrical and thermal conductivity, mechanical strength, impact toughness and anti-aging performance. In addition, the preparation method provided in the present invention is relatively simple, has low production equipment requirements and low implementation difficulty, and is easy to realize industrial production and manufacturing.
[0040] In summary, the present invention has the following advantages:
[0041] 1. The PC / ABS alloy material prepared in the present invention not only has good antistatic performance and thermal conductivity, but also has good mechanical strength, impact toughness and anti-aging performance.
[0042] 2. The self-made graphene and / or carbon nanotube doped modified polyaniline resin of the present invention can be used as an antistatic agent to improve the thermal conductivity and heat conductivity of the prepared PC / ABS alloy material. At the same time, the production cost of the antistatic agent is relatively low compared to graphene, which is convenient for reducing the production ingredient cost of the antistatic PC / ABS alloy material, and then facilitating the popularization and promotion of the antistatic PC / ABS alloy material in the market.
[0043] 3 In the preparation method of the present invention, the compatibilizer, toughening agent, surface-modified inorganic staple fiber composition, antistatic agent, coupling agent, antioxidant, PC resin, ABS resin and compatibilizer are dispersed and mixed uniformly through the mixing stage, thereby ensuring that the prepared PC / ABS alloy material has good electrical and thermal conductivity, mechanical strength, impact toughness and anti-aging properties.
[0044] 4 The preparation method of the present invention is relatively simple, has low requirements on production equipment and is easy to implement, and is easy to realize industrial production. DETAILED DESCRIPTION
[0045] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.
[0046] Preparation Example
[0047] Preparation Example 1: The antistatic agent is graphene-doped modified polyaniline resin.
[0048] The preparation method of graphene-doped modified polyaniline resin comprises the following steps:
[0049] Step 1: Purchase commercially available carboxylated graphene (Carboxylated graphene TimesGraph from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences TM , purity:>98wt%; thickness: 0.55~3.74nm; diameter: 0.5-3μm; number of layers: <10 layers; oxygen content:>10wt%);
[0050] Step 2: 2 g of carboxylated graphene was added to 48 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 50 g of graphene aqueous dispersion;
[0051] Step 3: fully dissolve 25 g of aniline in 800 g of 2.0 mol / L hydrochloric acid aqueous solution to prepare an aniline solution, and slowly add 20 g of graphene aqueous dispersion to the aniline solution at a dropping rate of 2 mL / min under 200 rpm magnetic stirring and nitrogen protection. After the addition of the graphene aqueous dispersion is completed, continue to stir magnetically at 200 rpm for 24 h to obtain a gray-black mixed emulsion;
[0052] Step 4: Cool the gray-black mixed emulsion to 0°C in an ice bath, maintain the temperature of the gray-black mixed emulsion at 0°C, add 400ppm (relative to 400ppm of the gray-black mixed emulsion mass) of ammonium persulfate to the gray-black mixed emulsion under 400rpm magnetic stirring, continue to stir magnetically at 400rpm for 12h, maintain the temperature of the gray-black mixed emulsion at 0°C and let it stand for 24h, polymerize to obtain a solution containing a black-green precipitate, then perform vacuum filtration to obtain a black-green precipitate, wash the black-green precipitate three times with deionized water and ethanol alternately, and separate the obtained black-green precipitate into a precipitate. The precipitate is dissolved in N-methylpyrrolidone to obtain an N-methylpyrrolidone solution with a black-green precipitate content of 10wt%, and 1wt% (relative to 1wt% of the mass of the N-methylpyrrolidone solution with a black-green precipitate content of 10wt%) of an activator diazino carbonate is added under magnetic stirring at 200rpm, and then the remaining 30g of the graphene aqueous dispersion is slowly added dropwise to the N-methylpyrrolidone solution with a black-green precipitate content of 10wt% at a dropping rate of 2mL / min, the temperature is raised to 60°C for reaction for 2h, and then the N-methylpyrrolidone and water are removed by reduced pressure distillation to obtain a black-green precipitate;
[0053] Step 5: After the obtained black-green precipitate is vacuum dried, it is placed in a planetary ball mill with zirconium oxide as grinding beads and ball milled at 80 rpm for 30 minutes under nitrogen to obtain the product antistatic agent.
[0054] Preparation Example 2: The antistatic agent is carbon nanotube-doped modified polyaniline resin.
[0055] The preparation method of carbon nanotube-doped modified polyaniline resin comprises the following steps:
[0056] Step 1, purchasing commercially available carboxylated carbon nanotubes (purchased from Guangdong Innovation Materials (Shenzhen) Co., Ltd.);
[0057] Step 2: 2 g of carboxylated carbon nanotubes were added to 48 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 50 g of carbon nanotube aqueous dispersion;
[0058] Step 3: fully dissolve 25 g of aniline in 800 g of 2.0 mol / L hydrochloric acid aqueous solution to prepare an aniline solution, and slowly add 20 g of carbon nanotube aqueous dispersion to the aniline solution at a dropping rate of 2 mL / min under magnetic stirring at 200 rpm and under nitrogen protection. After the addition of the carbon nanotube aqueous dispersion is completed, continue to stir magnetically at 200 rpm for 24 hours to obtain a gray-black mixed emulsion;
[0059] Step 4: Cool the gray-black mixed emulsion to 0°C under an ice bath, maintain the temperature of the gray-black mixed emulsion at 0°C, add 400ppm (relative to 400ppm of the gray-black mixed emulsion mass) of ammonium persulfate to the gray-black mixed emulsion under 400rpm magnetic stirring, continue to stir magnetically at 400rpm for 12h, maintain the temperature of the gray-black mixed emulsion at 0°C and stand for 24h, polymerize to obtain a solution containing a black-green precipitate, then perform vacuum filtration to obtain a black-green precipitate, wash the black-green precipitate three times with deionized water and ethanol alternately, and separate the obtained black-green precipitate into a precipitate; The precipitate is dissolved in N-methylpyrrolidone to obtain an N-methylpyrrolidone solution with a black-green precipitate content of 10wt%, and 1wt% (relative to 1wt% of the mass of the N-methylpyrrolidone solution with a black-green precipitate content of 10wt%) of an activator diazino carbonate is added under magnetic stirring at 200rpm, and then the remaining 30g of the carbon nanotube aqueous dispersion is slowly added dropwise to the N-methylpyrrolidone solution with a black-green precipitate content of 10wt% at a dropping rate of 2mL / min, the temperature is raised to 60°C for reaction for 2h, and then the N-methylpyrrolidone and water are removed by reduced pressure distillation to obtain a black-green precipitate;
[0060] Step 5: After the obtained black-green precipitate is vacuum dried, it is placed in a planetary ball mill with zirconium oxide as grinding beads and ball milled at 80 rpm for 30 minutes under nitrogen to obtain the product antistatic agent.
[0061] Preparation Example 3: The antistatic agent is graphene-doped modified polyaniline resin.
[0062] The preparation method of graphene-doped modified polyaniline resin comprises the following steps:
[0063] Step 1: Purchase commercially available hydroxylated graphene (Hydroxylated graphene TimesGraphene from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences TM , purity:>98wt%, thickness: 0.55~3.74nm, diameter: 0.5-3μm, number of layers: <10 layers, oxygen content:>10wt%);
[0064] Step 2: 1 g of hydroxylated graphene was added to 24 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 25 g of graphene aqueous dispersion;
[0065] Step 3: Dissolve 10 g of aniline in 300 g of 2 mol / L hydrochloric acid aqueous solution to prepare an aniline solution. Under 200 rpm magnetic stirring and nitrogen protection, slowly add 25 g of graphene aqueous dispersion to the aniline solution at a dropping rate of 2 mL / min. After the addition of the graphene aqueous dispersion is completed, continue to stir magnetically at 200 rpm for 24 h to obtain a gray-black mixed emulsion.
[0066] Step 4: Cool the gray-black mixed emulsion to 0°C under an ice bath, maintain the temperature of the gray-black mixed emulsion at 0°C, add 400ppm (400ppm relative to the mass of the gray-black mixed emulsion) of ammonium persulfate to the gray-black mixed emulsion under 400rpm magnetic stirring, continue to stir magnetically at 400rpm for 12h, and then maintain the temperature of the gray-black mixed emulsion at 0°C and stand for 24h. The polymerization reaction obtains a solution containing a black-green precipitate, and then vacuum filtration is performed to obtain a black-green precipitate, and the black-green precipitate is washed alternately with deionized water and ethanol three times. After the obtained black-green precipitate is vacuum dried, it is placed in a planetary ball mill, and zirconium oxide is used as grinding beads. The product antistatic agent can be obtained by ball milling at 80rpm under nitrogen for 30min.
[0067] Preparation Example 4: The antistatic agent is carbon nanotube-doped modified polyaniline resin.
[0068] The preparation method of carbon nanotube-doped modified polyaniline resin comprises the following steps:
[0069] Step 1, purchasing commercially available hydroxylated carbon nanotubes (purchased from Guangdong Innovation Materials (Shenzhen) Co., Ltd.);
[0070] Step 2: 1 g of hydroxylated carbon nanotubes was added to 24 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 25 g of carbon nanotube aqueous dispersion;
[0071] Step 3: Dissolve 15 g of aniline in 500 g of 1.8 mol / L hydrochloric acid aqueous solution to prepare an aniline solution. Under magnetic stirring at 200 rpm and under nitrogen protection, slowly add 25 g of the carbon nanotube aqueous dispersion to the aniline solution at a dropping rate of 2 mL / min. After the addition of the carbon nanotube aqueous dispersion is completed, continue to stir magnetically at 200 rpm for 24 hours to obtain a gray-black mixed emulsion.
[0072] Step 4: Cool the gray-black mixed emulsion to 0°C under an ice bath, maintain the temperature of the gray-black mixed emulsion at 0°C, add 400ppm (400ppm relative to the mass of the gray-black mixed emulsion) of ammonium persulfate to the gray-black mixed emulsion under 400rpm magnetic stirring, continue to stir magnetically at 400rpm for 12h, and then maintain the temperature of the gray-black mixed emulsion at 0°C and stand for 24h. The polymerization reaction obtains a solution containing a black-green precipitate, and then vacuum filtration is performed to obtain a black-green precipitate, and the black-green precipitate is washed alternately with deionized water and ethanol three times. After the obtained black-green precipitate is vacuum dried, it is placed in a planetary ball mill, and zirconium oxide is used as grinding beads. The product antistatic agent can be obtained by ball milling at 80rpm under nitrogen for 30min.
[0073] The difference between Preparation Example 5 and Preparation Example 1 is that the preparation method of graphene-doped modified polyaniline resin comprises the following steps:
[0074] Step 1, purchasing commercially available carboxylated graphene and commercially available aminated graphene (aminated graphene TNRGON from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, purity: >98wt%, thickness: 0.55-3.74nm, diameter: 0.5-3μm, number of layers: <10 layers, amino content: ~0.5wt%);
[0075] Step 2: 2 g of carboxylated graphene was added to 48 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 50 g of graphene aqueous dispersion A;
[0076] At the same time, 1 g of amino graphene was added to 24 g of deionized water and mechanically stirred at 240 rpm for 10 min, followed by ultrasonic dispersion treatment for 5 h (ultrasonic frequency 60 kHz, ultrasonic power 1200 W) to obtain 25 g of graphene aqueous dispersion B;
[0077] Step 3: fully dissolve 40 g of aniline in 1200 g of 2.0 mol / L hydrochloric acid aqueous solution to prepare an aniline solution, and slowly add 50 g of graphene aqueous dispersion A to the aniline solution at a dropping rate of 2 mL / min under 200 rpm magnetic stirring and nitrogen protection. After the addition of the graphene aqueous dispersion A is completed, continue to stir magnetically at 200 rpm for 24 h to obtain a gray-black mixed emulsion;
[0078] Step 4: Cool the gray-black mixed emulsion to 0°C under an ice bath, maintain the temperature of the gray-black mixed emulsion at 0°C, add 400ppm (relative to 400ppm of the gray-black mixed emulsion mass) of ammonium persulfate to the gray-black mixed emulsion under 400rpm magnetic stirring, continue to stir magnetically at 400rpm for 12h, maintain the temperature of the gray-black mixed emulsion at 0°C and stand for 24h, polymerize to obtain a solution containing a black-green precipitate, then perform vacuum filtration to obtain a black-green precipitate, and wash the black-green precipitate three times with deionized water and ethanol alternately. , dissolving the obtained black-green precipitate in N-methylpyrrolidone to obtain an N-methylpyrrolidone solution with a black-green precipitate content of 10wt%, adding a 1wt% hydrochloric acid aqueous solution under magnetic stirring at 200rpm to adjust the system pH value to 4, then slowly adding 25g of graphene aqueous dispersion B to the N-methylpyrrolidone solution with a drop rate of 2mL / min, heating to 60°C for reaction for 2h, adding a 1wt% sodium hydroxide aqueous solution for neutralization, and then removing N-methylpyrrolidone and water by reduced pressure distillation to obtain a black-green precipitate;
[0079] Step 5: After the obtained black-green precipitate is vacuum dried, it is placed in a planetary ball mill with zirconium oxide as grinding beads and ball milled at 80 rpm for 30 minutes under nitrogen to obtain the product antistatic agent.
[0080] The difference between Preparation Example 6 and Preparation Example 5 is that the commercially available aminated graphene is replaced by commercially available aminated carbon nanotubes (aminated carbon nanotubes TNMN2 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, -NH2 content: 0.45wt%, SSA:> 233m 2 / g, length: ~50 microns, OD: 8-15 nm).
[0081] Example
[0082] An antistatic PC / ABS alloy material containing a compatibilizer is prepared from the following raw materials in parts by weight: 80-100 parts of PC resin, 20-25 parts of ABS resin, 5-10 parts of a toughening agent, 4-8 parts of a compatibilizer, 20-30 parts of an inorganic staple fiber composition, 4-8 parts of an antistatic agent, 0.5-2 parts of a coupling agent, and 1-4 parts of an anti-aging agent.
[0083] Preferably, the antistatic PC / ABS alloy material is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent, 6 parts of compatibilizer, 28 parts of inorganic staple fiber composition, 6 parts of antistatic agent, 2 parts of coupling agent, and 3 parts of antioxidant.
[0084] The compatibilizer is ABS-g-MAH and / or styrene grafted maleic anhydride multipolymer.
[0085] Anti-aging agents include antioxidants and anti-ultraviolet agents.
[0086] The antioxidant is composed of antioxidant 1098, antioxidant 168 and silicon carbide whiskers and / or nano silicon nitride.
[0087] The anti-ultraviolet agent is composed of UV-531, UV-234 and titanium nitride.
[0088] The coupling agent is composed of a siloxane coupling agent and a titanate coupling agent. Preferably, the coupling agent is composed of a composite siloxane coupling agent and di(dioctylpyrophosphoryl)ethylene titanate in a mass ratio of (8-9):(1-2), and the composite siloxane coupling agent is prepared by reflux reaction of methacryloxysilane and aminosilane at 70-90°C for 2-4h.
[0089] The toughening agent is at least one of TPU, TPEE, TPV and MBS.
[0090] The inorganic short fiber composition comprises short glass fibers and short silicon carbide fibers.
[0091] Preferably, the inorganic short fiber composition is composed of chopped glass fibers, chopped silicon carbide fibers, and amino carbon nanotubes in a mass ratio of (30-40): (50-65): (5-10). The chopped glass fibers include chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm. The chopped silicon carbide fibers include chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm.
[0092] Preferably, the chopped glass fibers are composed of chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
[0093] Preferably, the chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
[0094] Further preferably, a conductive film is formed on the surface of the chopped glass fibers, and the conductive film is at least one of a polyaniline conductive film, a deposited metal film, and a conductive oxide film, wherein the deposited metal film is one of silver, copper, and aluminum.
[0095] The antistatic agent is graphene-doped modified polyaniline resin and / or carbon nanotube-doped modified polyaniline resin.
[0096] The preparation method of the antistatic agent comprises the following steps:
[0097] Step 1, obtaining carboxylated graphene and / or graphene carbon nanotubes: performing carboxylation modification treatment on graphene and / or carbon nanotubes, or purchasing commercially available carboxylated graphene and / or carboxylated carbon nanotubes;
[0098] Step 2: 1 part of carboxylated graphene and / or carboxylated carbon nanotubes is added to 20-25 parts of deionized water, mechanically stirred for 5-10 minutes, and then subjected to ultrasonic dispersion treatment for 3-6 hours to obtain an aqueous dispersion of graphene and / or carbon nanotubes;
[0099] Step 3: Dissolve 6-12 parts of aniline in 100-200 parts of 1-2 mol / L hydrochloric acid aqueous solution to prepare an aniline solution, and slowly drop the graphene and / or carbon nanotube aqueous dispersion into the aniline solution under magnetic stirring and nitrogen protection. After the dropwise addition is completed, continue magnetic stirring for 8-24 hours to obtain a gray-black mixed emulsion;
[0100] Step 4, cooling to 0-4°C in an ice bath, maintaining the temperature of the gray-black mixed emulsion between 0-4°C, adding 200-400ppm of initiator to the gray-black mixed emulsion under magnetic stirring, continuing magnetic stirring for 12-16h, maintaining the temperature of the gray-black mixed emulsion between 0-4°C and standing for 18-24h, polymerizing to obtain a solution containing a black-green precipitate, then vacuum filtering to obtain a black-green precipitate, washing the black-green precipitate three times with deionized water and ethanol alternately, and after vacuum drying the obtained black-green precipitate, placing it in a planetary ball mill for ball milling for 15-30min to obtain the product antistatic agent.
[0101] A method for preparing an antistatic PC / ABS alloy material containing a compatibilizer comprises the following steps:
[0102] Step 1, preparing a surface-modified inorganic staple fiber composition and an antistatic agent at the same time;
[0103] Step 2: uniformly mix the accurately measured PC resin, ABS resin, compatibilizer, toughening agent, surface-modified inorganic staple fiber composition, antistatic agent, coupling agent, and antioxidant, and then knead at 215-220° C. for 240-360 seconds to obtain a fluidized kneaded mixture;
[0104] Step three, putting the fluidized banburying mixture into a twin-screw extruder for melt extrusion, the temperature setting of the seven heating zones of the twin-screw extruder is as follows: zone one 200-210°C, zone two 220-230°C, zone three 235-240°C, zone four 245-250°C, zone five 250-255°C, zone six 250-255°C, zone seven 250-255°C, the screw speed is 300-500rpm, and the obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain an antistatic PC / ABS alloy material.
[0105] Example 1: An antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by weight: 80 parts of PC resin (SURLYN PC2000 DuPont, USA, tensile strength 14 MPa, elongation at break 760%, melt flow rate 4.5 g / 10 min), 20 parts of ABS resin (Chimei PA-709, Ningbo Rongsu New Materials Co., Ltd.), 6 parts of toughening agent TPU (BASF 1160D TPU resin), 6 parts of compatibilizer-ABS-g-MAH (G1606 of Foshan Zuogao Plastic Chemical Co., Ltd., ABS-G-MAH maleic anhydride grafted PC alloy compatibilizer), 28 parts of inorganic staple fiber composition, 6 parts of antistatic agent of Preparation Example 1, 1.6 parts of KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)ethylene titanate, 0.5 parts of nano silicon nitride (4N flaky high-purity nano silicon nitride powder, average particle size 50-200 nanometers , Hebei Wenlun Metal Materials Co., Ltd.), 0.5 parts of silicon carbide whiskers (diameter 0.1-1um length 5-30um, CAS No. 409-21-2, customized by Guangzhou Hongwu Materials Technology Co., Ltd.), 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, 0.3 parts of nano titanium nitride (average particle size 700nm, customized by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.). The inorganic staple fiber composition is composed of chopped glass fiber (437BMC chopped fiber, diameter 15-20 microns, customized length 2-3mm, customized by Shandong Taicheng Fiber Co., Ltd.) and chopped silicon carbide fiber (Tyranno SA third-generation silicon carbide fiber, Ube Industries, Japan, diameter 11 microns, customized length 2-3mm) in a mass ratio of 3:2.
[0106] A method for preparing an antistatic PC / ABS alloy material containing a compatibilizer comprises the following steps:
[0107] Step 1, preparing a surface-modified inorganic staple fiber composition: placing 30g of chopped glass fiber and 20g of chopped silicon carbide fiber in a 2L surface modifier aqueous solution and stirring evenly, the surface modifier aqueous solution is prepared with 16g of KH550, 4g of KH570, and 1980g of deionized water, and then performing ultrasonic dispersion treatment for 4h, the ultrasonic frequency is 85kHz, the ultrasonic power is 1500W, and after the ultrasonic dispersion is completed, vacuum drying is performed to obtain a surface-modified inorganic staple fiber composition;
[0108] At the same time, prepare an antistatic agent, referring to the preparation method of the antistatic agent in Preparation Example 1;
[0109] Step 2, accurately measuring PC resin, ABS resin, compatibilizer-ABS-g-MAH, toughening agent TPU, the surface-modified inorganic staple fiber composition in step 1, the antistatic agent in Preparation Example 1, KH570 coupling agent, di(dioctylpyrophosphoryl)ethylene titanate, nano silicon nitride, silicon carbide whisker, antioxidant 1098, antioxidant 168, UV-531, UV-770, and nano titanium nitride are mixed uniformly and then placed at 218° C. for 300 seconds to obtain a fluidized mixed mixture;
[0110] Step three, putting the fluidized internal mixing mixture into a twin-screw extruder for melt extrusion, the temperature setting of the seven heating zones of the twin-screw extruder is as follows: zone one 205°C, zone two 225°C, zone three 235°C, zone four 250°C, zone five 252°C, zone six 252°C, zone seven 252°C, the screw speed is 450rpm, and the obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain an antistatic PC / ABS alloy material.
[0111] The difference between Example 2 and Example 1 is that the inorganic staple fiber composition is composed of chopped glass fiber (437BMC chopped fiber, diameter 15-20 microns, customized length 2-3mm) and chopped silicon carbide fiber (beryllium-containing silicon carbide fiber of Hunan Boxiang New Materials Co., Ltd., diameter 13-15 microns, customized length 2-3mm) in a mass ratio of 3:2.
[0112] The difference between Example 3 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 90 parts of PC resin, 22 parts of ABS resin, 8 parts of toughening agent TPU, 7 parts of compatibilizer-ABS-g-MAH, 24 parts of inorganic staple fiber composition, 7 parts of the antistatic agent of Preparation Example 1, 1.6 parts of KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)titanate ethylene ester, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0113] The difference between Example 4 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 100 parts of PC resin, 25 parts of ABS resin, 10 parts of toughening agent TPU, 8 parts of compatibilizer-ABS-g-MAH, 30 parts of inorganic staple fiber composition, 8 parts of the antistatic agent of Preparation Example 1, 1.6 parts of KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)titanate ethylene ester, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0114] The difference between Example 5 and Example 1 is: Step 2, the accurately measured PC resin, ABS resin, compatibilizer-ABS-g-MAH, toughening agent TPU, the surface-modified inorganic staple fiber composition in Step 1, the antistatic agent in Preparation Example 1, KH570 coupling agent, di(dioctylpyrophosphoryl)titanate ethylene ester, nano-silicon nitride, silicon carbide whiskers, antioxidant 1098, antioxidant 168, UV-531, UV-770, and nano-titanium nitride are mixed evenly and then placed at 215°C for 360s to obtain a fluidized mixed mixture.
[0115] The difference between Example 6 and Example 1 is: Step 2, the accurately measured PC resin, ABS resin, compatibilizer-ABS-g-MAH, toughening agent TPU, the surface-modified inorganic staple fiber composition in Step 1, the antistatic agent in Preparation Example 1, KH570 coupling agent, di(dioctylpyrophosphoryl)titanate ethylene ester, nano-silicon nitride, silicon carbide whiskers, antioxidant 1098, antioxidant 168, UV-531, UV-770, and nano-titanium nitride are mixed evenly and then placed at 220°C for 240s to obtain a fluidized mixed mixture.
[0116] The difference between Example 7 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by the antistatic agent in Preparation Example 2.
[0117] The difference between Example 8 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by the antistatic agent in Preparation Example 3.
[0118] The difference between Example 9 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by the antistatic agent in Preparation Example 4.
[0119] The difference between Example 10 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by the antistatic agent in Preparation Example 5.
[0120] The difference between Example 11 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by the antistatic agent in Preparation Example 6.
[0121] The difference between Example 12 and Example 1 is that a conductive metal aluminum film is formed on the surface of the chopped glass fiber by chemical precipitation. The preparation method of the chopped glass fiber with a conductive metal aluminum film on the surface is as follows: 20g of aluminum nitrate nonahydrate is dissolved in 1.0L of deionized water and magnetically stirred at 200rpm for 30min, and then 50g of chopped glass fiber (437BMC chopped fiber, diameter 15-20 microns, customized length 2-3mm, customized by Shandong Taicheng Fiber Co., Ltd.) is added. After continuing to magnetically stir at 200rpm for 30min, a 3wt% aluminum hydroxide aqueous solution is added dropwise while maintaining magnetic stirring until Al 3+ After complete precipitation, the mixture was stirred magnetically at 200 rpm for 100 min and then allowed to stand for 24 h to obtain an Al(OH)3 / chopped glass fiber binary colloid. The Al(OH)3 / chopped glass fiber binary colloid was washed alternately three times with deionized water and acetone, and then filtered under reduced pressure to obtain a solid powder. The solid powder was placed in a vacuum drying oven, the drying temperature was adjusted to 120°C, and dried for 4 h. The solid was transferred to an atmosphere tube furnace for calcination. The temperature was increased to 620°C at 15°C / min and calcined for 250 min in an air atmosphere to obtain an Al2O3 / chopped glass fiber composite powder. A hydrogen-argon mixture was introduced into the atmosphere tube furnace, and the volume ratio of hydrogen to argon in the hydrogen-argon mixture was 1:4. The temperature was maintained at 620°C for reduction reaction for 4 hours, and the furnace was opened and naturally cooled to room temperature. The solid was placed in a planetary ball mill and ball milled at 60 rpm for 15 min to obtain a finished product having a chopped glass fiber composited with a conductive metal aluminum film on the surface.
[0122] The difference between Example 13 and Example 1 is that the inorganic short fiber composition is composed of chopped glass fiber (437BMC chopped fiber, diameter 15-20 microns, customized length 2-3mm, customized by Shandong Taicheng Fiber Co., Ltd.), chopped silicon carbide fiber (beryllium-containing silicon carbide fiber of Hunan Boxiang New Materials Co., Ltd., diameter 13-15 microns, customized length 2-3mm), amino carbon nanotubes (amino carbon nanotubes TNMN2 of Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, -NH2 content: 0.45wt%, SSA:>233m 2 / g, length: ~50microns, OD:8-15nm) with a mass ratio of 30:65:5.
[0123] The difference between Example 14 and Example 13 is that the inorganic short fiber composition is composed of chopped glass fiber, chopped silicon carbide fiber (Be-containing silicon carbide fiber from Hunan Boxiang New Materials Co., Ltd., with a diameter of 13-15 microns and a customized length of 2-3 mm), amino carbon nanotubes (amino carbon nanotubes TNMN2 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, with -NH2 content of 0.45wt%, SSA:>233m 2 / g, length: ~50microns, OD:8-15nm) with a mass ratio of 35:58:7.
[0124] The difference between Example 15 and Example 13 is that the inorganic short fiber composition is composed of chopped glass fiber, chopped silicon carbide fiber (Be-containing silicon carbide fiber from Hunan Boxiang New Materials Co., Ltd., with a diameter of 13-15 microns and a customized length of 2-3 mm), amino carbon nanotubes (amino carbon nanotubes TNMN2 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, with -NH2 content of 0.45wt%, SSA:>233m 2 / g, length: ~50microns, OD:8-15nm) with a mass ratio of 40:50:10.
[0125] The difference between Example 16 and Example 13 is that the chopped glass fibers in the inorganic staple fiber composition are composed of chopped glass fibers with a length of 1±0.2 mm (customized by Shandong Taicheng Fiber Co., Ltd.), chopped glass fibers with a length of 4-5 mm (customized by Shandong Taicheng Fiber Co., Ltd.), and chopped glass fibers with a length of 8-10 mm (customized by Shandong Taicheng Fiber Co., Ltd.) in a mass ratio of 20:60:20.
[0126] The difference between Example 17 and Example 16 is that the chopped glass fibers are composed of chopped glass fibers with a length of 1±0.2 mm, chopped glass fibers with a length of 4-5 mm, and chopped glass fibers with a length of 8-10 mm in a mass ratio of 30:65:15.
[0127] The difference between Example 18 and Example 16 is that the chopped glass fibers are composed of chopped glass fibers with a length of 1±0.2 mm, chopped glass fibers with a length of 4-5 mm, and chopped glass fibers with a length of 8-10 mm in a mass ratio of 40:35:25.
[0128] The difference between Example 19 and Example 13 is that the chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 1±0.2 mm (customized by Hunan Boxiang New Materials Co., Ltd.), chopped silicon carbide fibers with a length of 4±0.5 mm (customized by Hunan Boxiang New Materials Co., Ltd.), and chopped silicon carbide fibers with a length of 8-10 mm (customized by Hunan Boxiang New Materials Co., Ltd.) in a mass ratio of 20:60:20.
[0129] The difference between Example 20 and Example 13 is that the chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 1±0.2 mm, chopped silicon carbide fibers with a length of 4±0.5 mm, and chopped silicon carbide fibers with a length of 8-10 mm in a mass ratio of 30:65:15.
[0130] The difference between Example 21 and Example 13 is that the chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 1±0.2 mm, chopped silicon carbide fibers with a length of 4±0.5 mm, and chopped silicon carbide fibers with a length of 8-10 mm in a mass ratio of 40:35:25.
[0131] The difference between Example 22 and Example 20 is that the inorganic short fiber composition is composed of short glass fiber, short silicon carbide fiber, amino carbon nanotube (amino carbon nanotube TNMN2 from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, -NH2 content: 0.45wt%, SSA:> 233m 2 / g, length: ~50microns, OD: 8-15nm) with a mass ratio of 35:58:7. The chopped silicon carbide fiber is composed of chopped silicon carbide fiber with a length of 1±0.2mm, chopped silicon carbide fiber with a length of 4±0.5mm, and chopped silicon carbide fiber with a length of 8-10mm with a mass ratio of 30:65:15. The chopped glass fiber is composed of chopped glass fiber with a length of 1±0.2mm, chopped glass fiber with a length of 4-5mm, and chopped glass fiber with a length of 8-10mm with a mass ratio of 30:65:15.
[0132] The difference between Example 23 and Example 22 is that the coupling agent KH570 is replaced by a composite siloxane coupling agent. The composite siloxane coupling agent is prepared by reflux reaction of methacryloxysilane KH570 and aminosilane KH550 at 80° C. for 3 hours.
[0133] Comparative Example
[0134] The difference between Comparative Example 1 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent TPU-BASF 1160D, 6 parts of compatibilizer-ABS-g-MAH, 28 parts of inorganic staple fiber composition, 6 parts of antistatic agent of Preparation Example 1, 1.6 parts of coupling agent KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)ethylene titanate, 1.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.8 parts of UV-531, and 0.2 parts of UV-770.
[0135] The difference between Comparative Example 2 and Comparative Example 1 is that in the preparation method of the antistatic PC / ABS alloy material, the banburying treatment of step 2 is not performed, and the melt extrusion, wire drawing cooling, granulation, and drying of step 3 are directly performed to obtain the antistatic PC / ABS alloy material.
[0136] The difference between Comparative Example 3 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent TPU, 6 parts of compatibilizer-ABS-g-MAH, 28 parts of chopped glass fiber (437BMC chopped fiber, diameter 15-20 microns, customized length 2-3mm), 6 parts of the antistatic agent of Preparation Example 1, 1.6 parts of KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)titanate ethylene ester, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0137] The difference between Comparative Example 4 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent TPU, 6 parts of compatibilizer-ABS-g-MAH, 28 parts of chopped silicon carbide fiber (beryllium-containing silicon carbide fiber of Hunan Boxiang New Materials Co., Ltd., with a diameter of 13-15 microns and a customized length of 2-3 mm), 6 parts of the antistatic agent of Preparation Example 1, 1.6 parts of KH570 coupling agent, 0.4 parts of di(dioctylpyrophosphoryl)titanate ethylene ester, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0138] The difference between Comparative Example 5 and Example 1 is: Step 2, the accurately measured PC resin, ABS resin, compatibilizer-ABS-g-MAH, toughening agent TPU, the surface-modified inorganic staple fiber composition in Step 1, the antistatic agent in Preparation Example 1, KH570 coupling agent, di(dioctylpyrophosphoryl)titanate ethylene ester, nano-silicon nitride, silicon carbide whiskers, antioxidant 1098, antioxidant 168, UV-531, UV-770, and nano-titanium nitride are mixed evenly and then placed at 210°C for 300s to obtain a fluidized mixed mixture.
[0139] The difference between Comparative Example 6 and Example 1 is: Step 2, the accurately measured PC resin, ABS resin, compatibilizer-ABS-g-MAH, toughening agent TPU, the surface-modified inorganic staple fiber composition in Step 1, the antistatic agent in Preparation Example 1, KH570 coupling agent, di(dioctylpyrophosphoryl)titanate ethylene ester, nano-silicon nitride, silicon carbide whiskers, antioxidant 1098, antioxidant 168, UV-531, UV-770, and nano-titanium nitride are mixed evenly and then placed at 225°C for 240s to obtain a fluidized mixed mixture.
[0140] The difference between Comparative Example 7 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent TPU, 6 parts of compatibilizer-ABS-g-MAH, 28 parts of inorganic staple fiber composition, 6 parts of the antistatic agent of Preparation Example 1, 2 parts of KH570 coupling agent, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0141] The difference between Comparative Example 8 and Example 1 is that an antistatic PC / ABS alloy material containing a compatibilizer is made of the following raw materials in parts by mass: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent TPU, 6 parts of compatibilizer-ABS-g-MAH, 28 parts of inorganic staple fiber composition, 6 parts of the antistatic agent of Preparation Example 1, 2 parts of KH550 coupling agent, 0.5 parts of nano-silicon nitride, 0.5 parts of silicon carbide whiskers, 0.8 parts of antioxidant 1098, 0.2 parts of antioxidant 168, 0.5 parts of UV-531, 0.2 parts of UV-770, and 0.3 parts of nano-titanium nitride.
[0142] The difference between Comparative Example 9 and Example 1 is that the antistatic agent in Preparation Example 1 is replaced by a commercially available polyaniline resin (conductive polyaniline, Wuhan Huaxiang Kejie Biotechnology Co., Ltd., CAS No. 5612-44-2).
[0143] Performance testing
[0144] 1. Test method for tensile strength and elongation at break: The tensile strength and elongation at break of antistatic PC / ABS alloy materials are measured according to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics". 2. Test method for notched impact strength: The notched impact strength of antistatic PC / ABS alloy materials is measured according to the cantilever beam impact strength test method according to GB / T 1843-2010. 3. Test method for flexural strength: The flexural strength of antistatic PC / ABS alloy materials is measured according to GB / T 9341-2008 "Determination of flexural properties of plastics". 4. Test method for thermal conductivity: The thermal conductivity of antistatic PC / ABS alloy materials is measured according to ISO 22007-4 method, test conditions: 23°C. 5. Surface resistivity The surface resistivity of antistatic PC / ABS alloy materials is measured using ZST-121 volume surface resistivity tester. The test results are shown in Table 1.
[0145] Table 1: Test results of antistatic PC / ABS alloy materials in Examples and Comparative Examples
[0146]
[0147]
[0148]
[0149]
[0150] Combining Example 1 and Comparative Example 1 with Table 1, it can be seen that the addition of nano silicon nitride, silicon carbide whiskers, and nano titanium nitride has a significant effect on improving the overall heat-resistant oxygen degradation performance. In the banburying section, nano silicon nitride, silicon carbide whiskers, and nano titanium nitride can improve the heat-resistant oxygen degradation performance of the molecular chain segments of PC resin, ABS resin, toughening agent TPU, and antistatic agent, thereby ensuring the mechanical strength and impact toughness of the prepared antistatic PC / ABS alloy material, and are also key additives that can be subjected to banburying and mixing treatment in the preparation method. Banburying and mixing treatment can make the inorganic staple fiber composition and inorganic filler in the formula dispersed and mixed more evenly, thereby effectively improving the mechanical strength, impact toughness, thermal conductivity, and electrical conductivity of the antistatic PC / ABS alloy material.
[0151] It can be seen from Examples 1, 5-6 and Comparative Examples 5-6 and Table 1 that the banburying temperature range in the present invention is preferably controlled at 215-220°C and the banburying time is preferably controlled at 240-360s, which can ensure that the antistatic PC / ABS alloy material has relatively excellent mechanical strength, impact toughness, thermal and electrical conductivity, and aging resistance.
[0152] It can be seen from Example 1 and Comparative Examples 3-4 and Table 1 that the inorganic staple fiber composition is mainly composed of chopped glass fibers and chopped silicon carbide fibers, and the prepared antistatic PC / ABS alloy material has relatively good mechanical strength, impact toughness, thermal and electrical conductivity, aging resistance, and the overall production cost is low.
[0153] It can be seen from Example 1, Examples 22-23 and Comparative Examples 7-8 and Table 1 that the coupling agent is composed of a composite siloxane coupling agent and di(dioctylpyrophosphoryl)ethylene titanate in a mass ratio of (8-9):(1-2), and the prepared antistatic PC / ABS alloy material has relatively good mechanical strength, impact toughness, thermal and electrical conductivity, and aging resistance.
[0154] It can be seen from Example 1 and Example 2 and Table 1 that the domestic short-fiber silicon carbide fiber has met the mechanical properties and electrical and thermal conductivity requirements of the antistatic PC / ABS alloy material in the present invention. The use of domestic short-fiber silicon carbide fiber to replace the short-fiber silicon carbide fiber imported from Japan can reduce the overall production cost.
[0155] It can be seen from Example 1, Examples 7-11 and Comparative Example 9 and Table 1 that the self-made antistatic agent in the present invention can improve the electrical and thermal conductivity of the antistatic PC / ABS alloy material, and also has a positive effect on the mechanical properties and impact toughness of the antistatic PC / ABS alloy material.
[0156] It can be seen from Example 1 and Example 12 and Table 1 that the antistatic PC / ABS alloy material prepared by using chopped glass fibers with a conductive metal aluminum film composited on the surface has better electrical and thermal conductivity.
[0157] It can be seen from Example 1 and Examples 13-15 and Table 1 that the antistatic PC / ABS alloy material prepared by the inorganic short fiber composition composed of chopped glass fiber, chopped silicon carbide fiber and amino carbon nanotubes in a mass ratio of (30-40):(50-65):(5-10) has relatively better mechanical strength, impact toughness, thermal and electrical conductivity, and aging resistance, but excessive addition of amino carbon nanotubes will affect the overall impact toughness.
[0158] It can be seen from Example 1 and Examples 13-15, Examples 16-18 and Table 1 that the antistatic PC / ABS alloy material can be further optimized in terms of mechanical strength, impact toughness, thermal and electrical conductivity, and aging resistance based on the fact that the inorganic staple fiber composition is composed of chopped glass fibers, chopped silicon carbide fibers, and amino carbon nanotubes in a mass ratio of (30-40):(50-65):(5-10), and the chopped glass fibers in the inorganic staple fiber composition are composed of chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
[0159] In combination with Example 1 and Example 13-15, Example 19-22 and Table 1, it can be seen that based on the inorganic short fiber composition consisting of chopped glass fiber, chopped silicon carbide fiber, and amino carbon nanotubes in a mass ratio of (30-40): (50-65): (5-10), and the chopped silicon carbide fiber in the inorganic short fiber composition is composed of chopped silicon carbide fiber with a length of 0.5-2mm, chopped silicon carbide fiber with a length of 3-6mm, and chopped silicon carbide fiber with a length of 8-15mm in a mass ratio of (20-40): (35-65): (15-25), the mechanical strength, impact toughness, thermal and electrical conductivity, and aging resistance of the antistatic PC / ABS alloy material can be further optimized. In summary, the PC / ABS alloy material prepared in the present invention not only has good antistatic performance and thermal conductivity, but also has good mechanical strength, impact toughness, and aging resistance. It can be seen from this that Example 22 is the best technical solution.
[0160] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. An antistatic PC / ABS alloy material containing a compatibilizer, characterized in that: It is made of the following raw materials in parts by weight: 80-100 parts of PC resin, 20-25 parts of ABS resin, 5-10 parts of toughening agent, 4-8 parts of compatibilizer, 20-30 parts of inorganic staple fiber composition, 4-8 parts of antistatic agent, 0.5-2 parts of coupling agent, and 1-4 parts of antioxidant; the compatibilizer is ABS-g-MAH and / or styrene grafted maleic anhydride multipolymer; the antioxidant is composed of antioxidant and anti-ultraviolet agent; the antioxidant is composed of antioxidant 1098, antioxidant 168, silicon carbide whisker and nano silicon nitride; the anti-ultraviolet agent is composed of UV-531, UV-234 and titanium nitride; the coupling agent is composed of silane coupling agent and titanate coupling agent; the toughening agent is at least one of TPU, TPEE, TPV and MBS; the inorganic staple fiber composition contains chopped glass fiber and chopped silicon carbide fiber; The preparation method of the antistatic agent comprises the following steps: step 1, obtaining surface activated graphene and / or surface activated carbon nanotubes: performing surface activation treatment on graphene and / or carbon nanotubes, so that one of hydroxyl, carboxyl and amino groups is generated on the surface of graphene and / or carbon nanotubes; step 2, adding 1 mass part of carboxylated graphene and / or carboxylated carbon nanotubes into 20-25 mass parts of deionized water, mechanically stirring for 5-10 minutes, and then performing ultrasonic dispersion treatment for 3-6 hours to obtain an aqueous dispersion of graphene and / or carbon nanotubes; step 3, fully dissolving 6-12 mass parts of aniline in 100-200 mass parts of 1-2 mol / L hydrochloric acid aqueous solution to prepare an aniline solution, and stirring under magnetic stirring and nitrogen protection, The graphene and / or carbon nanotube aqueous dispersion is slowly added dropwise to the aniline solution, and after the addition is completed, magnetic stirring is continued for 8-24 hours to obtain a gray-black mixed emulsion; step 4, cooling to 0-4°C in an ice bath, maintaining the temperature of the gray-black mixed emulsion between 0-4°C, adding 200-400ppm of initiator under magnetic stirring, continuing magnetic stirring for 12-16 hours, and maintaining the temperature of the gray-black mixed emulsion between 0-4°C for 18-24 hours, and polymerizing to obtain a solution containing a black-green precipitate, and then filtering under reduced pressure to obtain a black-green precipitate, washing three times with deionized water and ethanol alternately, and then vacuum drying and placing in a planetary ball mill for ball milling for 15-30 minutes to obtain an antistatic agent; The preparation method of the antistatic PC / ABS alloy material containing a compatibilizer comprises: step 1, preparing a surface-modified inorganic staple fiber composition and an antistatic agent at the same time; step 2, uniformly mixing accurately measured PC resin, ABS resin, compatibilizer, toughening agent, surface-modified inorganic staple fiber composition, antistatic agent, coupling agent, and anti-aging agent, and then mixing at 215-220° C. for 240-360 seconds to obtain a fluidized mixed material; step 3, mixing the fluidized dense The refined mixed material is put into a twin-screw extruder for melt extrusion. The set temperatures of seven heating zones of the twin-screw extruder are: 200-210°C for zone one, 220-230°C for zone two, 235-240°C for zone three, 245-250°C for zone four, 250-255°C for zone five, 250-255°C for zone six, and 250-255°C for zone seven. The screw speed is 300-500rpm. The molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain an antistatic PC / ABS alloy material.
2. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 1, characterized in that: The antistatic PC / ABS alloy material comprises the following raw materials in parts by weight: 80 parts of PC resin, 20 parts of ABS resin, 6 parts of toughening agent, 6 parts of compatibilizer, 28 parts of inorganic staple fiber composition, 6 parts of antistatic agent, 2 parts of coupling agent, and 3 parts of anti-aging agent.
3. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 1 or 2, characterized in that: The inorganic short fiber composition is composed of chopped glass fibers, chopped silicon carbide fibers, and amino carbon nanotubes in a mass ratio of (30-40):(50-65):(5-10); the chopped glass fibers include chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm; the chopped silicon carbide fibers include chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm.
4. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 3, characterized in that: The chopped glass fibers are composed of chopped glass fibers with a length of 0.5-2 mm, chopped glass fibers with a length of 3-6 mm, and chopped glass fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
5. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 3, characterized in that: The chopped silicon carbide fibers are composed of chopped silicon carbide fibers with a length of 0.5-2 mm, chopped silicon carbide fibers with a length of 3-6 mm, and chopped silicon carbide fibers with a length of 8-15 mm in a mass ratio of (20-40):(35-65):(15-25).
6. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 3, characterized in that: A conductive film is formed on the surface of the chopped glass fibers; the conductive film is at least one of a polyaniline conductive film, a deposited metal film, and a conductive oxide film; the deposited metal film is one of silver, copper, and aluminum.
7. The antistatic PC / ABS alloy material containing a compatibilizer according to claim 1, characterized in that: The coupling agent is composed of a composite silane coupling agent and di(dioctylpyrophosphoryl)ethylene titanate in a mass ratio of (8-9):(1-2); the composite silane coupling agent is prepared by reflux reaction of methacryloxysilane and aminosilane at 70-90° C. for 2-4 hours.
8. A method for preparing an antistatic PC / ABS alloy material containing a compatibilizer according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, preparing a surface-modified inorganic staple fiber composition and an antistatic agent at the same time; Step 2: uniformly mix the accurately measured PC resin, ABS resin, compatibilizer, toughening agent, surface-modified inorganic staple fiber composition, antistatic agent, coupling agent, and antioxidant, and then knead at 215-220° C. for 240-360 seconds to obtain a fluidized kneaded mixture; Step three, putting the fluidized banburying mixture into a twin-screw extruder for melt extrusion, the temperature setting of the seven heating zones of the twin-screw extruder is as follows: zone one 200-210°C, zone two 220-230°C, zone three 235-240°C, zone four 245-250°C, zone five 250-255°C, zone six 250-255°C, zone seven 250-255°C, the screw speed is 300-500rpm, and the obtained molten extruded material is subjected to wire drawing, cooling, granulation and drying to obtain an antistatic PC / ABS alloy material.
Citation Information
Patent Citations
Plastic product and preparation method thereof, and heat-dissipatable shell
CN106118042A
Antistatic PC-ABS (polycarbonate-acrylonitrile butadiene styrene) alloy material and preparation method thereof
CN109504057A